FROM PANDEMIC DISRUPTION TO POST-PANDEMIC TRANSFORMATION: NEW POSSIBILITIES FOR TEACHING IN SOUTH AFRICAN HIGHER EDUCATION. - Brodie, K.; Joffe, A.; Dukhan, S.; Godsell, S.; de Klerk, D.; Padayachee, K. (South African Journal of Higher Education, 2022)
The COVID-19 pandemic has had previously unimaginable and far-reaching effects on higher education globally (Baker et al. 2022; Cranfield et al. 2021; Kara 2021; Le Grange 2020). On top of the widespread loss felt by students and teachers across the world, we have had to make rapid changes to previously taken-for-granted ways of doing, being, learning and teaching (Baker et al. 2022; Cranfield et al. 2021). Emergency Remote Teaching and Learning (ERTL) brought constraints and opportunities, challenges and innovations. This article gives form to the statement: "there is an opportunity in the moment for genuine equity-focused innovation in policy-making, provision and pedagogy" (Czerniewicz et al. 2020). We use a theoretical framework of structure, culture and agency through which to view possibilities for transformation of pedagogy, and a form of semi-autoethnography as methodology. Two lecturers, one in the Humanities (Education) and one in the Life Sciences, wrote extended narratives of their experiences of ERTL and the other authors then posed a series of questions to the story authors, which elicited a set of analytic descriptions and explanations. Through iterations of this analysis, we identified two important themes: attending to students' socio-emotional needs and developing students' engagement, selfregulation and reflexivity. The analysis identifies key opportunities and challenges that these required and how they were addressed by the lecturers concerned. Based on the analysis and drawing on Case's (2015b) argument for an expanded sense of agency for students, we argue that the lecture is a key structural and cultural element of the university space that was disrupted during the pandemic and can be transformed going forward. We thus argue for decentering the lecture. Furthermore, we argue that care and concern for students has not been a primary cultural element of teaching and learning in higher education, for structural reasons, and that it should be an integral part of pedagogies going forward.